Coping Stress on Students Working on Thesis: Is it Related to Social Support? - Asfira Eka Yulia Ningsih; Ramon Ananda Paryontri (Edumaspul: Jurnal Pendidikan, 2023)
This study uses correlational analysis as a quantitative research method. This research was conducted because the thesis writing process is widely regarded as a demanding phase that can cause stress among students. Social support is a viable coping strategy for individuals to effectively manage and navigate stressful situations. The purpose of this study was to determine the relationship between social support and stress management in students doing their final assignment at the Faculty of Psychology and Education, Universitas Muhammadiyah Sidoarjo. The research sample consisted of 501 senior students who were completing their thesis at the Faculty of Psychology and Education, Universitas Muhammadiyah Sidoarjo. A total of 272 samples were obtained using the Isaac and Michael sampling method. The scale used in this study is the social support scale and coping stress scale. The research data collection methodology uses two measurements, namely the social support scale which consists of 30 items with a reliability coefficient of 0.792, and the coping stress scale which consists of 37 items with a reliability coefficient of 0.830. This study proposes a hypothesis about the potential for a positive correlation between social support and coping stress in students who are working on their thesis at the Faculty of Psychology and Education, Muhammadiyah University of Sidoarjo. The results showed a correlation coefficient of 0.639 and a significance level of 0.000 ± 0.05.